Diversity and conservation of indigenous and minor vegetables - Bhardwaj, D R; Gautam, K. K.; Dubey, R. K.; Chaubey, T.; Pandey, S.; Singh, Ashok K (Indian Horticulture, 2020)
The Indian gene centre has vast diversity of indigenous and minor vegetables in edible and wild/weedy form. Indiscriminate extraction of biological material from the wild threatens their survival, even to the extent of pushing some species into extinction. It is true that once they disappear; there is no alternative source for acquiring the unique qualities they provide. It is hence, important to develop sustainable harvesting and conservation regimes that do not undermine the capability of a plant species to survive in the wild. The scientists have shown great concern over the conservation and preservation of environment, biodiversity and ecosystem in a sustainable manner.